Peanuts thrive on fungi - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Improvements are on the way for Mozambique s important groundnut (Arachis hypogaea) crops which have suffered from periods of drought in recent years. Orlando Quilambo, biologist and scientific research director at the Eduardo Mondlane University...